PTH-054 The rising incidence of early-onset paediatric inflammatory bowel disease (PARIS A1A) in scotland since 1981: a national, population-based, cohort study. (22nd June 2015) - Henderson, P; Cameron, FL; Jagger, F; Hansen, R; Drummond, HE; Reynish, E; Loganathan, S; Russell, RK; Satsangi, J; Wilson, DC
Abstract : Introduction: Although worldwide and Scottish 1 data has clearly shown a persistent rise in paediatric inflammatory bowel disease (PIBD), population-based trends in early-onset incident PIBD (i.e. diagnosed before their 10 th birthday; Paris A1a) are lacking. We aimed to evaluate the incidence of PIBD A1a between 1981–2013 using a complete national cohort study. Method: National data from previously published incident cohorts of PIBD in Scotland during 1981–1995 and 2003–2008 were first examined; prospectively collected incident cases from 2009–2013 were also included. Patients were only included following thorough case-note review. As IBD-unclassified (IBDU) was not a recognised IBD type in the earlier cohorts, the classification of non-Crohn's colitis (NCC; i.e. ulcerative colitis and IBDU combined) was introduced to allow comparisons. Incidence rates were calculated using publicly available population data and trends across cohorts calculated using Poisson regression. Results: 402 A1a PIBD patients were identified with a slight (53%) male preponderance; approximately 60% were Crohn's disease (CD) with the remainder NCC. There was a steady increase in incident cases with 39 patients diagnosed between 1981–1985 and 134 between 2008–2013. The adjusted incidence of A1a PIBD rose from 1.2/100, 000/yr (95% CI 0.8–1.6) (1981–1985) to 4.1/100, 000/yr (95% CI 3.5–4.7) (2008–2013) (p < 0.001); the incidence rate remainded stable in the most recent epoch (2008–2013). The incidence of the 0–5 yr group rose from 0.7/100, 000/yr (1981–1985) to 2.0/100, 000/yr (2008–2013) (p = 0.017) compared to an incidence rise of 2.0/100, 000/yr (1981–1985) to 7.2/100, 000/yr (2008–2013) (p < 0.001) in the 6–9 yr group. The incident rate ratio between the first and last epochs were 2.9 (95% CI 1.5–6.4) and 3.6 (95% CI 2.3–5.8) in the 0–5 yr and the 6–9 yr age groups respectively. There were no significant sex differences across any group and both the CD and NCC groups showed similar trends. Conclusion: Using population-based Scottish data from the previous four decades we have shown that early-onset PIBD (A1a) has shown a significant rise in incidence, with three-fold increases seen in both the very-early-onset (0–5 yr) and 6–9 yr age groups. However, incidence rates seem to have stabilised in the last decade, despite a sustained rise in overall PIBD. 1 Further examination of these young patients may provide clues to IBD aetiopathogenesis. Disclosure of interest: None Declared. References: Henderson P, et al . J Crohns Colitis . 2015;9 (S1):S2 Benchimol, et al . Gastroenterology 2014;147(4):803–813